2019
DOI: 10.3390/ijerph16214235
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella in Retail Food and Wild Birds in Singapore—Prevalence, Antimicrobial Resistance, and Sequence Types

Abstract: Non-typhoidal salmonellosis is a leading cause of foodborne zoonosis. To better understand the epidemiology of human salmonellosis, this study aimed to determine the prevalence, antimicrobial resistance and sequence types of Salmonella in retail food and wild birds (proximity to humans) in Singapore. We analyzed 21,428 cooked and ready-to-eat food and 1,510 residual faecal samples of wild birds collected during 2010–2015. Thirty-two Salmonella isolates from food and wild birds were subjected to disc diffusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 42 publications
(47 reference statements)
1
28
3
Order By: Relevance
“…The serovar has been isolated from a wide variety of sources including poultry, reptiles, fish, mushrooms and turtles [27]. Two monophasic strains belonging to the MLST sequence types ST42 and ST423 were isolated in Singapore from local wild birds (black bittern and crow) in 2012 [28]. In 2018, the serovar 4,5,12:b:-(dT+) was reported to be responsible for a multistate outbreak of Salmonella infection due to consumption of products containing Kratom, a tropical plant native to Southeast Asia [29].…”
Section: Discussionmentioning
confidence: 99%
“…The serovar has been isolated from a wide variety of sources including poultry, reptiles, fish, mushrooms and turtles [27]. Two monophasic strains belonging to the MLST sequence types ST42 and ST423 were isolated in Singapore from local wild birds (black bittern and crow) in 2012 [28]. In 2018, the serovar 4,5,12:b:-(dT+) was reported to be responsible for a multistate outbreak of Salmonella infection due to consumption of products containing Kratom, a tropical plant native to Southeast Asia [29].…”
Section: Discussionmentioning
confidence: 99%
“…While ST11 had been reported in humans, poultry, food, and some wild animal species, including reptiles in many countries from Asia, Africa, South America, and European countries (enterobase). Notably, ST1925 has been reported to be a single cell variant of ST11, and both sequence types are known to be geographically widespread and have previously been reported in foods, humans and animals [23,24]. The detection of these STs from different sources may also indicate their ability to adapt to, and persist in different hosts or types of samples.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of these STs from different sources may also indicate their ability to adapt to, and persist in different hosts or types of samples. The detection of ST11 in foods may imply possible transmission from neighboring countries like Singapore and China, where the ST type prevails [24]. In this study, the Whole-Genome Sequencing platform was used for the MLST analysis against the traditional PCR based MLST, followed by Sanger sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…15 Ciprofloxacin has previously been suggested as first-line treatment of NTS infections, as this antibiotic accumulates intracellularly where Salmonella pathogens tend to grow. 15 However, a Singaporebased study 16 demonstrated a 35.3% resistance to quinolones among NTS isolates versus a 5.9% resistance to co-amoxiclav. Hence, the use of co-amoxiclav as first-line treatment of NTS infections may be preferred in a Singaporean population.…”
Section: Discussionmentioning
confidence: 99%